Impact occupational factors on safety and health through ergonomic approach among older taxi drivers in Malaysia - Md Yusoff, Irwan syah; Ismail, M. H.; Rohaizahtulamni, R. (Malaysian Public Health Physicians, 2022)
One of the alternative professions that may include the older is taxi drivers. Subsequently, they have to take explicit thought during driving activities as indicated by their capacity and ability to sustain their lives while minimizing health problems and increasing safety. Therefore, this paper aimed to study from a user experience the impact of occupational factors on safety and health by an ergonomic approach among older taxi drivers in Malaysian. A cross-sectional study was led utilizing a self-administered survey instrument. Purposive method sampling was used based on inclusive criteria; age 60 years old and above, self-driving taxi more than one year, no disabilities, and registered with the Ministry of Transport. A total of 443 respondents participated in the study. SPSS software version 20.0 to analyse the data. More than half of the respondents (70.0%) felt back pain in the past 12 months, and 75.4% in the last seven days. There is a significant relationship health problem (p< 0.05) between variables; BMI, smoking status, carrying luggage into the trunk, supporting of the backrest for the whole body, the effect of the seat size on comfortable driving, feeling of back pain is mainly due to the seat design and long-distance driving and driving posture analysis at the high-risk position and awkward body posture on seat design during handling task. The low implication awareness on ergonomics education could increase health problems and decrease safety while handling the task among older taxi drivers in Malaysia.